The Association Between Sleep Duration and Arrest Among Adolescents - Partin, Raymond (Crime & delinquency, 2023)
In recent years, sleep duration has received increased scrutiny with respect to criminologically relevant outcomes. No attention, however, has been given to the possible relationship between sleep duration and the likelihood of arrest. Given the negative downstream effects that arrest may have on adolescents, this is an important relationship to investigate. To this end, the current study uses data from the 2018 Florida Youth Substance Abuse Survey (N?=?49,360), and the results indicate that severe sleep deficiencies are positively associated with self-reported arrest, whereas minor deficiencies and excess sleep are not. Discussion focuses on the implications and limitations of these findings as well as a call for better integration of health behaviors into criminological analyses.